ANALYSIS OF POTASSIUM INTAKE, DIET COMPLIANCE AND NUTRITIONAL STATUS OF CHRONIC KIDNEY FAILURE PATIENTS WITH HEMODIALYSIS AT JASA KARTINI HOSPITAL, TASIKMALAYA CITY - Listianasari, Yanita; Camila, Nizma (Program Studi Ilmu Gizi, Jurusan Kesmas Fakultas Ilmu-Ilmu Kesehatan Universitas Jenderal Soedirman, 2025)
Chronic kidney failure is a gradual and irreversible kidney dysfunction characterized by a permanent decrease in kidney function. The study aims to analyze potassium intake, dietary compliance and nutritional status of chronic kidney failure patients with hemodialysis at Jasa Kartini Hospital, Tasikmalaya City. The type of study is an analytical survey with a cross-sectional study approach, namely the variables of potassium intake, dietary compliance and nutritional status were studied simultaneously which was conducted from April to May 2024. Potassium intake data were obtained by interview using a 2 x 24 hour food recall form and a food photo book. Dietary compliance data were obtained by interview using a dietary compliance questionnaire. Nutritional status data were obtained using the SGA formular. The results of the study showed that most of the potassium intake in patients was in the good category as many as 39 people (59%). Most respondents were compliant with the diet as many as 40 people (61%). The conclusion is that most chronic kidney failure patients with hemodialysis have good potassium intake, many are compliant with the diet and nutritional status is at risk of malnutrition.